The dilemma to complaint: a critique of the Transfer of functions from Indecopi to Susalud in respect of medical and insurance services - Segovia Trocones, Enzo (2018)
In this article, the author analyzes the distribution of functions between SuSalud and Indecopi, regarding the mandates of Legislative Decree 1158. In particular, the author addresses the functions of administrative regulation related to infractions in the provision of health services by the private sector in our national scope.This is done taking into account considerations that are inherent to a fundamental right as the right to health, which implies an active duty for the State as a whole. This is the reason why intense criticisms are raised about the way in which the distribution of functions has been regulated among public administration bodies, through confusing rules that signifi cantly increase the costs faced by consumers to present their complaints.